Pelaksanaan Pembelajaran Ruang Lingkup Materi Permainan Bola Kecil pada Masa Pandemi di Sekolah Dasar di Kecamatan Welahan Kabupaten Jepara - Husaini, Faisal Fahri; Pujianto, Agus (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to determine the implementation of learning the scope of the small ball game material during the pandemic in Elementary Schools in Welahan District, Jepara Regency including planning, implementation, evaluation and learning creativity. Using qualitative research with a descriptive approach, triangulation data collection techniques through observation, interviews and documentation, data sources consist of 8 elementary schools. The results of the research on learning planning teachers have made syllabus, lesson plans, teaching materials, learning media, LKPD, assessment instruments, the implementation of offline learning is carried out once a week, learning evaluations have been carried out covering 3 aspects, namely cognitive, affective and psychomotor, learning creativity is carried out closely. simplification of basic techniques, game rules and how to play. The conclusion of the research for learning planning in the category is quite good because the teacher has prepared learning tools, the implementation of learning is in the good category because it can run in a pandemic condition, the evaluation of learning in the category is quite good which includes cognitive, affective and psychomotor aspects and the creativity of learning in the good category includes simplification of basic techniques, regulations games and how to play.